Evolution of the bovine milk fatty acid profile – From colostrum to milk five days post parturition. (May 2020) - O'Callaghan, Tom F.; O'Donovan, Michael; Murphy, John P.; Sugrue, Katie; Mannion, David; McCarthy, William P.; Timlin, Mark; Kilcawley, Kieran N.; Hickey, Rita M.; Tobin, John T.
Abstract: Milk was collected from each of 18 cows (presenting an even spread of 1st, 2nd and 3rd lactation): colostrum on the day of calving and subsequent morning milk 1–5 days post parturition. Days post parturition significantly affected the fatty acid profile of colostrum and transition milk samples. The colostrum fatty acid profile was distinctly different from that of mature milk, with significantly higher levels of polyunsaturated and saturated fatty acids. Parity of the cow had a significant effect on the fatty acid profile of colostrum and transition milk samples; conjugated linoleic acid was significantly higher in cows entering their 1st lactation than in those in their 3rd lactation, while multiparous cows produced significantly higher concentrations of C16:0. The changing composition of the fatty acid profile can be classed into three distinct phases: colostrum (D0), transition milk (D1 and D2 post parturition) and mature milk (D3–D5).